NOMINA BERPEMARKAH PARTIKEL O DALAM BAHASA JEPANG - Lina Rosliana (KIRYOKU, 2018)
(Title: Noun Marked by Case Particle O in Japanese).   Noun in Japanese is a part of speech that can stand alone, not conjugated, and can occupy the function of the subject, object, as well as predicate in the sentence. Nomina can be named of goods, place name, person's name, profession, number, and others. This diversity makes the nouns in Japanese have different markers, one of which is the case particle o. Basically, case particle o in Japanese have a function as a marker of objects. However, the object function occupied by nouns is not just a target. Noun in Japanese can also be a word related to place or time. This study aims to examine the types of nouns marked by case particle o in Japanese. This research uses the method of distribution studies with agih techniques where the object is the language element studied. This study consists of three stages, namely data collection, data analysis, and data presentation. The data collected in the form of phrases with the construction of N + Po + V from various data sources online and print. The next step is to analyze the data collected by using the basic grouping of nouns from Moriyama (2008). The data that have been analyzed will be presented in descriptive form.Keywords : Noun, Case Particle o, Japanese